2014
DOI: 10.1186/1743-0003-11-29
|View full text |Cite
|
Sign up to set email alerts
|

Cortical activation change induced by neuromuscular electrical stimulation during hand movements: a functional NIRS study

Abstract: ObjectivesNeuromuscular electrical stimulation (NMES) has been used in the field of rehabilitation for a long time. Previous studies on NMES have focused on the peripheral effect, in contrast, relatively little is known about the effect on the cerebral cortex. In the current study, we attempted to investigate the change of cortical activation pattern induced by NMES during execution of hand movements in normal subjects, using functional near infrared spectroscopy (fNIRS).MethodsTwelve healthy normal subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…The results of EEG time-frequency analysis at the C3 electrode are presented in Figure 2. When the NMES current exceeded the motor threshold the EEG oscillations in the alpha band were clearly depressed (Figure 2D), consistent with numerous previous studies (Blickenstorfer et al, 2009; Jang et al, 2014). However, even with a stimulation current intensity lower than the motor threshold, the alpha band EEG oscillation was also depressed during NMES (Figures 2A–C).…”
Section: Resultssupporting
confidence: 91%
“…The results of EEG time-frequency analysis at the C3 electrode are presented in Figure 2. When the NMES current exceeded the motor threshold the EEG oscillations in the alpha band were clearly depressed (Figure 2D), consistent with numerous previous studies (Blickenstorfer et al, 2009; Jang et al, 2014). However, even with a stimulation current intensity lower than the motor threshold, the alpha band EEG oscillation was also depressed during NMES (Figures 2A–C).…”
Section: Resultssupporting
confidence: 91%
“…However, we found that the oxy-Hb concentration of the left SMA, right PrG, PoG, and SMA in ESC tasks significantly decreased compared with those without ESC. Jang et al (2014) have demonstrated that cortical activation of the sensorimotor cortex was decreased by neuromuscular ES. They suggested that the results were related to the motor learning effect.…”
Section: Discussionmentioning
confidence: 99%
“…The main disadvantage is that it does not evaluate infracortical layers, because light has a optimal penetration-scattering rate of 2 cm deep, suffering influence of the extracerebral superficial layers (Hoshi, 2016; Nguyen et al, 2016). Some authors postulate that fNIRS is a preferable tool to evaluate cortical activation induced by any type of electrical stimulation because it is less sensitive to electrical interference when compared to other neuroimaging techniques (Jang et al, 2014). fNIRS evaluating SSC can also be used to discriminate different stimulations, like handshake and cold temperature, as it presents different patterns of hemodynamic responses (Hong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%